2009
DOI: 10.1016/j.ijgo.2009.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Cytology versus HPV testing for the detection of high‐grade cervical lesions in women found positive on visual inspection in Mumbai, India

Abstract: Cytology and HPV testing were both found to be accurate triaging methods for women suspected of having CIN on visual inspection, especially for those with CIN 3 lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A possible reason could be the harbouring of cervical HPV infection without any visually detectable changes. A study from India [12] also stated that both cytology and HPV testing were found to be accurate for triaging or as a sequential method for women suspected of having high-grade lesions on visual inspection. The present study findings are not in agreement with this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible reason could be the harbouring of cervical HPV infection without any visually detectable changes. A study from India [12] also stated that both cytology and HPV testing were found to be accurate for triaging or as a sequential method for women suspected of having high-grade lesions on visual inspection. The present study findings are not in agreement with this.…”
Section: Discussionmentioning
confidence: 99%
“…One study assessed optimal screening strategies for cervical cancer using stand-alone tests and their combinations among low-and middle-income populations of Latin America and Eastern Europe [11]. Another study from India compared Pap and HPV tests for the detection of high-grade CIN among VIA-positive cases [12]. A recent study [13] demonstrated the need for triage testing on the primary selfsample HPV testing to identify clinically significant pre-cancers or cancers.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Referral of all the screen positives (many of whom are false positives) for colposcopy will result in substantial costs for the health-care systems and may create unnecessary anxiety in the women and their families. [ 6 ] Colposcopy services are still available only to a limited extent, with most of these facilities concentrated in the urban areas. Hence, there is need to triage the women screened positive on visual-based techniques with test with higher specificity to reduce referrals for colposcopy.…”
Section: Introductionmentioning
confidence: 99%